2021
DOI: 10.3390/agronomy11091706
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Forage Potential of the Global Collection of Finger Millet (Eleusine coracana (L.) Gaertn.) Germplasm Conserved at the ICRISAT Genebank

Abstract: Finger millet is an important drought-tolerant and grain-nutrient dense food crop grown in semi-arid regions in Asia and Africa. The forage is used as a source of dry roughage for feeding livestock. In this study, the finger millet diversity panel (310 accessions and four controls) representing the global collection of the finger millet germplasm conserved at the ICRISAT gene bank was assessed for forage quality and diversity in the years 2018 and 2019. Results of the study suggested that finger millet can gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
(65 reference statements)
0
0
2
Order By: Relevance
“…Among the treatment combinations, the numerically highest ME of finger millet straw (8.54 MJ kg −1 ) was recorded when 25% Finger millet was intercropped with 75% Vicia atropurpurea. ME obtained in the current study was higher than the findings of Backiyalakshmi et al. (2021) who reported 6.18%–6.89% in the assessment of forage potential of the Global collection of finger millet germplasm conserved at the ICRISAT genebank.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Among the treatment combinations, the numerically highest ME of finger millet straw (8.54 MJ kg −1 ) was recorded when 25% Finger millet was intercropped with 75% Vicia atropurpurea. ME obtained in the current study was higher than the findings of Backiyalakshmi et al. (2021) who reported 6.18%–6.89% in the assessment of forage potential of the Global collection of finger millet germplasm conserved at the ICRISAT genebank.…”
Section: Discussioncontrasting
confidence: 91%
“…Among the treatment combinations, the numerically highest ME of finger millet straw (8.54 MJ kg À1 ) was recorded when 25% Finger millet was intercropped with 75% Vicia atropurpurea. ME obtained in the current study was higher than the findings of Backiyalakshmi et al (2021) who reported 6.18%-6.89% in the assessment of forage potential of the Global collection of finger millet germplasm conserved at the ICRISAT genebank. The difference could be attributed to the cropping system (cereal-legume intercropping), the variety of finger millet used, soil nutrient, rainfall amount and pattern, and other macro and microenvironments.…”
Section: Metabolizable Energy Of Finger Milletcontrasting
confidence: 91%
“…Observations on ear shape with droopy, open, compact and semi-compact suggested the presence of all cultivated races (elongata, plana, compacta and vulgaris) of E. coracana ssp. coracana (Upadhyaya et al, 2006;Bharathi, 2011;Sood et al, 2019;Backiyalakshmi et al, 2021). Our observations for other qualitative traits were similar as in core and mini- core collections of global accessions (Upadhyaya et al, 2010), in Sri Lankan accessions (Dasanayaka and Kaluthanthri, 2017;Kumari et al, 2018), in north-west Indian accessions (Kumar et al, 2019) and in global collections from ICRISAT (Malambane and Jaisil, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Descriptive statistics such as range, mean and CV of various quantitative variables suggested wide variability within 300 accessions of the Nepalese collection. Mean flowering data ranged from 75 to 140 days which was narrower than in the global collections which included wild species (41-164 days) (Bharathi, 2011) but wider than in the core collection (51-96 days), the minicore subsets (51-93 days) (Upadhyaya et al, 2010) and in a global collection of 314 accessions (51-97 days) (Backiyalakshmi et al, 2021). Since our research was conducted at higher altitudes, we observed mean flowering time of 112 days (pooled mean of three sites) which is higher than in studies conducted at lower elevations, which reported 79 days (Bhattarai et al, 2014), 89 days (Bastola et al, 2015) and 74 days (Backiyalakshmi et al, 2021).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation